Exogenous melatonin enhances tomato heat resistance by regulating photosynthetic electron flux and maintaining ROS homeostasis - Sun, Cong; Meng, Sida; Wang, Baofeng; Zhao, Siting; Liu, Yulong; Qi, Mingfang; Wang, Zhenqi; Yin, Zepeng; Li, Tianlai (Plant physiology and biochemistry, 2023)
Heat stress reduces plant growth and reproduction and increases agricultural risks. As a natural compound, melatonin modulates broad aspects of the responses of plants to various biotic and abiotic stresses. However, regulation of the photosynthetic electron transfer, reactive oxygen species (ROS) homeostasis and the redox state of redox-sensitive proteins in the tolerance to heat stress induced by melatonin remain largely unknown. The oxygen evolution complex activity on the electron-donating side of photosystem II (PSII) is inhibited, and the electron transfer process from QA to QB on the electron-accepting side of PSII is inhibited. In this case, heat stress decreased the chlorophyll content, carbon assimilation rate, PSII activity, and the proportion of light absorbed by tomato seedlings during electron transfer. The ROS burst led to the breakdown of the PSII core protein. However, exogenous melatonin increased the net photosynthetic rate by 11.3% compared with heat stress, substantially reducing the restriction of photosynthetic systems induced by heat stress. Additionally, melatonin reduces the oxidative damage to PSII by balancing electron transfer on the donor, reactive center, and acceptor sides. Melatonin was used under heat stress to increase the activity of the antioxidant enzyme and preserve ROS equilibrium. In addition, redox proteomics also showed that melatonin controls the redox levels of proteins involved in photosynthesis, and stress and defense processes, which enhances the expression of oxidative genes. In conclusion, melatonin via controlling the photosynthetic electron transport and antioxidant, melatonin increased tomato heat stress tolerance and aided plant growth. •MT alleviated the oxidative damage of PSII by balancing the electron transfer of the donor side, reaction center, and receptor side.•MT inhibited ROS accumulation by promoting the key enzyme activities of AsA-GSH cycle, and modulating redox state of redox-sensitive proteins.•MT regulates the redox proteins of heat resistant signaling pathway and increases the expression of oxidative genes in downstream.